2016
DOI: 10.1007/s13361-016-1567-x
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of Monoisotopic Elements for Calibration in (TOF) Mass Spectrometry

Abstract: Abstract. Precise calibration in TOF MS requires suitable and reliable standards, which are not always available for high masses. We evaluated inorganic clusters of the monoisotopic elements gold and phosphorus (Au n + /Au n -and P n + /P n -) as an alternative to peptides or proteins for the external and internal calibration of mass spectra in various experimental and instrumental scenarios. Monoisotopic gold or phosphorus clusters can be easily generated in situ from suitable precursors by laser desorption/i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…The phosphorus clusters detected were in agreement with previous results of Bulgakov et al and Sladkova et al Previously, we reported that phosphorus clusters can provide a wide range of masses and are highly promising as a calibrants for complex samples, e.g. biological fluids or peptide mixtures, and, moreover, they can even serve as a suitable matrix . An overview of the intensity distribution of the clusters is shown in Figure .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The phosphorus clusters detected were in agreement with previous results of Bulgakov et al and Sladkova et al Previously, we reported that phosphorus clusters can provide a wide range of masses and are highly promising as a calibrants for complex samples, e.g. biological fluids or peptide mixtures, and, moreover, they can even serve as a suitable matrix . An overview of the intensity distribution of the clusters is shown in Figure .…”
Section: Resultssupporting
confidence: 91%
“…biological fluids or peptide mixtures, and, moreover, they can even serve as a suitable matrix. 25 An overview of the intensity distribution of the clusters is shown in Figure 4. All spectra were accumulated using 1000 profiles (laser shots).…”
Section: Mass Spectra Of Phosphorus Allotropesmentioning
confidence: 99%
“…Spectra were recorded using the reflectron in positive and negative ion mode in the m/z ranges of 100–400, 250–1200, and 800–3500. Calibration was carried out using red phosphorus clusters . A stainless steel sample target was used, containing 384 sample spots with a diameter of 2.8 mm.…”
Section: Methodssupporting
confidence: 90%
“…Overlapping MS peaks are common in complex samples like biological tissues when analyzed without a previous chromatographic separation stage. This results in a reduction of mass accuracy for TOF instruments preventing to obtain mass errors in the range of 5 ppm as described for non-overlapping MS signals[39].…”
Section: Results: Msi Of Animal Tissues With Gold-sputtered Layersmentioning
confidence: 99%